Evaluation of the visibility distance with the Istram program on third-class roads with a high accident rate - Barzola, L. (2023)
In Peru there are many roads where accidents occur due to their inadequate geometric design. The traffic accidents with the most incidents are of the side collision or collision type with a percentage of 42.73%, and distraction with 20.19% [1]. This shows that it is necessary to carry out a redesign on this road that seeks to reduce the percentage of accidents in the area. For the case study, a section of a 3km highway located in Santiago de Chuco, north of the city of Lima, was used. Thanks to the photogrammetric record of the current state of the road, sectors with geometric deficiencies were identified, such as visibility distance and safety in terms of precariousness in the use of signaling. Likewise, the evaluation carried out in the stopping and overtaking visibility distance concludes that with a constant speed of 30 km/h there are stretchs or sections that do not meet the necessary distance for its route.